OPTIMIZING MOSQUES AS CENTERS OF COMMUNITY EMPOWERMENT THROUGH PARTICIPATORY ACTION RESEARCH: EVIDENCE FROM KEDUNGBANTENG VILLAGE, MALANG, INDONESIA - Joko Wibowo (Suluh Adiluhung Publisher (SAPub), 2026)
Structural and sustainable programs that would allow mosques to serve as Centers of Community Empowerment are lacking in many mosques. This study provides optimal mosque role enhancements through Improved Mosque Governance; Increased Youth Participation; and Improvement in Legal Awareness Related to Waqf Management. Participatory Action Research (PAR) was the methodology used to collect data by way of Surveys, Interviews, Observations, and Focus Group Discussions involving; Mosque Administrators, Youth Participants and Community Leaders. The results of the study have shown that there have been significant gains in Mosque Governance Improvements, with 60% of all takmir now using Structured Administrative and Financial Systems; Youth Participation has increased from 30% to 65%; there has been successful legalization of Waqf Assets (AIW); as well as community engagement increases through Integrated Educational, Health & Social Programs.